Optical and electronic properties of germanium – silicon solid solutions - Smirnova, Olga Yu.; Stelmach, Georgy F.; Pokotilo, Yuri M.; Petukh, Alla N.; Markevich, Vladimir P.; Korolik, Olga V.; Mazanik, Alexander V. (Journal of the Belarusian State University. Physics, 2019)
The electronic and structural properties of Ge1-xSix solid solutions (x = 0 - 0.062) grown by the Czochralski methodand implanted with proton were studied using deep level transient spectroscopy (DLTS) and Raman scattering. It wasfound that with an increase of the silicon fraction in the solution, the single-phonon peak corresponding to Ge-Gevibrations shifts in the Raman spectra to lower frequencies with a rate ΔωGe - Ge/Δx = (31,3 ± 0,7) cm-1, and the tempe-rature of the maximum of the DLTS peak for the main radiation defect at aconstant electron emission rate en increases. The corresponding rate of increase in the free activation energy for electron emission is ΔEe/Δx = (2,9 ± 0,1) eV. The correlation between increasing Si content and decreasing in the lattice constant of Ge1- xSix, corresponding to Vegardʼs law a(x)= aGe-(aGe-aSi)x = 5,623 (0,25 ± 0,3)x Å, was found from the Raman peak shift in the anharmonic approximationfor the atomic interaction in a crystal. Alinear dependence of the change in the activation energy of a defect on the latticeparameter ΔEe/Δa = (1,6 ± 0,2) meV/Å was found to occur. It was shown that an increasing in the ionization energy ofdefect is associated with a decreasing in the average length of the Ge-Ge bond.